(untitled) (Transactions of the Association of European Schools of Planning, 2019)
Pilot projects are implemented to obtain results and knowledge that can be reused subsequently. In this paper, we address the question of the efficient and effective distribution of insights between pilot projects. We present detailed considerations on the structures which are required to share the results and knowledge obtained through evaluations of the stages of pilot projects. By establishing such structures, the reuse of existing knowledge is significantly simplified. A common structure for pilot projects allows for information sharing between equal stages of simultaneously running pilot projects. If the obtained knowledge of these individual stages is easily accessible, the need to review a comprehensive final project report is eliminated. For future pilot projects and large-scale projects, the costs associated with reusing existing knowledge is reduced and the cost-benefit ratio improves. We exemplify this by investigating systematic information sharing between equally structured pilot projects.